Soil aggregate stablity, organic carbon and plant available nutrient contents (N,P) in soils of prehistoric mounds after abandonment of cultivation - Botos, Ágnes; Ökrös, Vivien; Tóth, Csaba (Acta Geographica Debrecina Landscape & Environment series, 2015)
Prehistoric mounds are valuable archeological and nature conservational sites of the Hungarian lowland. However, due to the machinery cultivation most of them were plowed during the 20th century. After setting new legislative frames of their preservation, former cultivated mounds were abandoned and spontaneous regeneration processes of vegetation and soil could initiate on the ex lege mounds. Four mounds situated within the National Park of Hortobágy were investigated after their cultivation were abandoned, regarding their most important soil properties such as aggregate stability, bulk density, nitrogenous and phosphorous content, pH, organic carbon content and secondary carbonates.